Information and Communication Technology in Education Interactive Multi-Media Instructional Strategies for Teaching-Learning Process - Pushpanadham, K.; Khirwadkar, Anjali (New Delhi Sarup & Sons, 2022)
ICT In Education : Nature and Scope